Comparison of Neck Injury Criteria Values Across Human Body Models of Varying Complexity - Johnson, Dale; Koya, Bharath; Gayzik, F. Scott (Frontiers in Bioengineering and Biotechnology, 2020)
Due to the severity and frequency of cervical spine injuries, the neck injury criterion (Nij) was developed to provide a quantitative relationship between forces and moments of the upper neck with accompanied injury risk. The present study was undertaken to evaluate differences in calculated Nij for the Global Human Body Model Consortium’s detailed and simplified average 50th percentile male models. The simplified model is a computationally light version of the more detailed model and therefore it is of interest to achieve similar Nij values between the two models. These models were compared in 15 match paired conditions of rigid head impact and a mixture of 7 full body rigid hub and sled pulses, for 44 total simulations. Collectively, Nij values of the simplified model were found to exhibit a second-degree polynomial fit, allowing for a conversion to the prediction of the detailed model. Correlates were also derived for impact and inertial loading cases individually, for which the latter may be the subject of future work. The differences in Nij may be attributed to a variety of modeling approach differences related to neck muscles (attachment location and morphometric implementation), localization of head mass within the M50-OS, head geometry, and intervertebral joint space properties. With a primary focus on configurations in the anterior-posterior direction, there is a potential limitation in extensibility to lateral loading cases. In response to the relatively low Nij values exhibited, future work should evaluate the appropriateness of the established critical intercepts of Nij for computational human body models.